Transplanted gender norms and their limits in Monica Ali’s Brick Lane - Hasan, Md. Mahmudul (IIUM Press, International Islamic University Malaysia, 2018)
In Brick Lane (2003), Monica Ali describes both the spatial and metaphysical geography of Bangladeshi immigrants living in the diaspora in Britain. Face-to-face with immigrant anxieties as well as material constraints in the host society, diasporic patriarchy seeks to transplant gender norms of its country of origin and imposes domestic seclusion on women under its control. Against such a cultural backdrop, Ali depicts the problem of identity and gendered expectations of women in the diaspora. There is a persistent concern over women’s nomadic existence in patriarchal society and over their profound loss of confidence and cultural belonging. This specific, cultural pattern finds a concrete expression in Ali’s description of the transplantation of Bangladeshi gender ideology in London, as the novel unravels its limits and inefficacy in the postcolonial world of information technology.